Characterization of the Wetting and Dewetting Behavior of Powders - Subhash Chander; Richard Hogg; Douglas W. Fuerstenau (KONA Powder and Particle Journal, 2014)
Experimental procedures for characterizing the wetting behavior of powders are reviewed. The fundamental processes involved in wetting–passage from one state of two-phase equilibrium (solid/gas and liquid/gas) through a three-phase condition (solid/liquid/gas) to a second two-phase condition (solid/liquid and liquid/gas)–are evaluated. A brief discussion of the use of chemical agents such as surfactants to control wetting/dewetting behavior is also included. Characterization procedures, ranging from direct measurement of three-phase contact angles to indirect measures based on observation of the behavior of particles at liquid/gas interfaces are described. For large pieces of solid, contact angles can be determined by direct observation of liquid drops or gas bubbles in contact with polished surfaces. The problems associated with applications of this approach to packed beds of powder are discussed. A procedure for estimating apparent contact angles from the relative partitioning of small particles across an interface is presented. Estimation procedures based on static and dynamic measurements of liquid penetration into powder beds are evaluated. While indirect methods do not generally provide values of well-defined quantities such as contact angles, when appropriately selected they can yield quantitative information directly relevant to practical applications. Various indirect methods including film flotation, the Hallimond tube, bubble pick-up, induction time, immersion/sink time, imbibition time and wetting rate are described. Investigation of wetting phenomena at the molecular scale using techniques such as atomic force microscopy is discussed.